Modeling of electric springs and their multi-objective voltage control based on continuous genetic algorithm for unbalanced distribution networks. (June 2022) - Tapia-Tinoco, Guillermo; Granados-Lieberman, David; Valtierra-Rodriguez, Martin; Gabriel Avina-Cervantes, Juan; Garcia-Perez, Arturo
Highlights: This work proposes a multi-objective voltage control for multiple Electric Springs (ESs) in active unbalanced distribution systems. This multi-objective voltage control relies on a robust ES model, a modified backward/forward solution method (BFSM), and a continuous genetic algorithm (CGA). The proposed ES model is suitable for unbalanced conditions and can be implemented at any network location in single-, two-, and three-phase connections. It considers the self and mutual effects of the distribution line and the power flow of the elements connected at the point of common coupling (PCC) to determine the ES output voltage. Abstract: This work proposes a multi-objective voltage control for multiple Electric Springs (ESs) in active unbalanced distribution systems, where the goal is to provide a suitable simulation scheme to control the ESs in real-time applications. This multi-objective voltage control relies on a robust ES model, a modified backward/forward solution method (BFSM), and a continuous genetic algorithm (CGA). The proposed ES model is suitable for unbalanced conditions and can be implemented at any network location in single-, two-, and three-phase connections. Also, it considers the self and mutual effects of the distribution line (DL) and the power flow of the elements connected at the point of common coupling (PCC) to determine the ES output voltage. The ES model is adapted to the BFSM to quickly and reliably solve the power flow in the distribution network. Besides, the CGA simultaneously solves the mode of operation and the amount of reactive power exchange of the ESs to minimize power losses, voltage unbalance, and voltage deviation. The proposed voltage control is evaluated on an active distribution network based on a modified IEEE 13-bus for considering both load variations and power intermittences.